1996
DOI: 10.1074/jbc.271.51.32951
|View full text |Cite
|
Sign up to set email alerts
|

cDNA Cloning and Sequencing Reveal the Major Horse Allergen Equ c1 to Be a Glycoprotein Member of the Lipocalin Superfamily

Abstract: The gene encoding the major horse allergen, designated Equus caballus allergen 1 (Equ c1), was cloned from total cDNA of sublingual salivary glands by reverse transcription-polymerase chain reaction using synthetic degenerate oligonucleotides deduced from N-terminal and internal peptide sequences of the glycosylated hair dandruff protein. A recombinant form of the protein, with a polyhistidine tail, was expressed in Escherichia coli and purified by immobilized metal affinity chromatography. The recombinant pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
71
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 53 publications
5
71
1
Order By: Relevance
“…Crystallization and Data Collection-Protein expression, purification, and crystallization of recombinant sublingual gland (rSLG) Equ c 1 have been previously described (3,4). Briefly, rSLG Equ c 1 was expressed as a His-tagged protein in Escherichia coli, purified by metalion affinity chromatography, treated with factor Xa to excise the His tag, and concentrated to 6.0 mg/ml for crystallization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystallization and Data Collection-Protein expression, purification, and crystallization of recombinant sublingual gland (rSLG) Equ c 1 have been previously described (3,4). Briefly, rSLG Equ c 1 was expressed as a His-tagged protein in Escherichia coli, purified by metalion affinity chromatography, treated with factor Xa to excise the His tag, and concentrated to 6.0 mg/ml for crystallization.…”
Section: Methodsmentioning
confidence: 99%
“…Equ c 1 belongs to the lipocalin family (3,4). Although members of this family display low sequence similarity (often lower than 20% of amino acid identities), all share a conserved folding pattern, an 8-stranded ␤-barrel flanked by an ␣-helix at the C-terminal end of the polypeptide chain.…”
mentioning
confidence: 99%
“…The allergens are found in the mane, transpiration and urine. The major allergen of horse dander is Equ c1 (455,456). Cross-sensitization can sometimes be found with other equidae (pony, mule, donkey and zebra) and with cat, dog and guinea pig albumins.…”
Section: Other Mitesmentioning
confidence: 99%
“…In recent years, a number of allergens have been identified that stimulate IgE production and cause IgEmediated disease (6)(7)(8)(9). Although considerable information exists on the identification, purification, and cloning of inhaled allergens (pollens, dust mites, animal danders, insects, and fungi), few food allergens have been identified and studied.…”
Section: Introductionmentioning
confidence: 99%